Enhanced Public Auditing for Code-Based Multi-server Cloud (International Journal of Engineering and Computer Science, 2017)
cloud computing is a storing and accessing data and programs over the Internet instead of computer's hardware. Cloudcomputing is gaining popularity because it provides various on demand services which is location independent. Cloud user can store theirdata on cloud server remotely. So the data storage is resided with third party cloud service provider. In such situation, maintaining theprivacy of user’s data from unauthorized users is not an easy task. Before storing the data on the cloud server, the data can be encrypted.Using privacy preserving public auditing, data hosting service also brings new security threats toward users data, thus making individualsor enterprisers still feel hesitant. Sometimes data owners lose ultimate control over the fate of their outsourced data so there is risk thatavailability and integrity of the data might be lost. To protect outsourced data in cloud storage against corruptions, adding fault tolerance tocloud storage together with data integrity checking and failure reparation. Due to lower repair bandwidth while providing fault toleranceRegenerating codes have gained popularity